2023
DOI: 10.1002/pro.4573
|View full text |Cite
|
Sign up to set email alerts
|

Resolving the enthalpy of protein stabilization by macromolecular crowding

Abstract: Proteins in the cellular milieu reside in environments crowded by macromolecules and other solutes. Although crowding can significantly impact the protein folded state stability, most experiments are conducted in dilute buffered solutions. To resolve the effect of crowding on protein stability, we use 19 F nuclear magnetic resonance spectroscopy to follow the reversible, two-state unfolding thermodynamics of the N-terminal Src homology 3 domain of the Drosophila signal transduction protein drk in the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 57 publications
6
21
0
Order By: Relevance
“…For the large-sized PEG molecules, soft interactions did not play a significant role. 30 This is similar to what we observe for the hydrophilic polymers where we find that the preferential binding coefficients of the C state are higher than those of the E state. In another study, the RNA structure was found to be stabilized in crowded solutions of PEG via enthalpic stabilization.…”
Section: ■ Discussion and Conclusionsupporting
confidence: 90%
See 3 more Smart Citations
“…For the large-sized PEG molecules, soft interactions did not play a significant role. 30 This is similar to what we observe for the hydrophilic polymers where we find that the preferential binding coefficients of the C state are higher than those of the E state. In another study, the RNA structure was found to be stabilized in crowded solutions of PEG via enthalpic stabilization.…”
Section: ■ Discussion and Conclusionsupporting
confidence: 90%
“…It was shown that ethylene glycol and small oligomers of polyethylene glycol (PEG) bind to both folded and unfolded states via attractive interactions; however, stronger attraction to the folded state is observed that stabilizes the folded state. For the large-sized PEG molecules, soft interactions did not play a significant role . This is similar to what we observe for the hydrophilic polymers where we find that the preferential binding coefficients of the C state are higher than those of the E state.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Indeed, weak interactions complicate the interpretation of ensemble experiments, where different protein (or nucleic acid) conformations cannot be resolved. However, single-molecule measurements ,,, and carefully designed ensemble experiments , can leverage such interactions to explore the interplay between purely entropic effects and enthalpic contributions. In this respect, the use of cytomimetic solutions based on polymers and other solutes can provide physical insights into the properties of the cellular medium .…”
Section: Discussionmentioning
confidence: 99%